Aplikasi Administrasi Pembangunan Infrastruktur Desa Berbasis Web Pada Desa Tanjung Dalam - Jeni Afrillah; Yuntari Purbasari; Khana Wijaya (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Tanjung Dalam Village is one of the villages under the auspices of the Rambang sub-district, Muara Enim district. In this agency, the activities carried out include recording village infrastructure development activities using computerized recording using computer programs, namely in file data collection carried out using Microsoft Excel as a form of village head archive reports. However, sometimes data collection is only done using books as material for recording data so that data collection is inefficient and can cause errors in recording. The research method uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, documentation and literature study. The types of data consist of qualitative and data sources consist of primary and secondary. The development method is using the waterfall method, while the design tool uses UML which consists of use case diagrams, activity diagrams and class diagrams. This application will make it easy for officers to record data on the infrastructure development of Tanjung Dalam Village.